Using Citrus limon Extract and Evaluation of the Antibacterial Properties - Saad Ali Hussein Al-Akabi; Aliea K. Al-Masoodi; Ibtisam Abdulnabi Jasim (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The escalating prevalence of antibiotic-resistant bacteria necessitates the exploration of natural antimicrobial alternatives. Specific Background: Citrus limon (lemon) peel contains bioactive phytochemicals with potential antibacterial properties, yet systematic evaluation against clinical isolates remains limited. Knowledge Gap: Comparative efficacy of different extraction solvents and their mechanisms against multidrug-resistant pathogens require comprehensive investigation. Aims: This study evaluated antibacterial activities of aqueous, ethanolic, and methanolic extracts of C. limon peel against clinically isolated Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, and Klebsiella pneumoniae. Results: Ethanolic extract demonstrated superior antibacterial activity with inhibition zones of 19.5 ± 0.3 mm against S. aureus and 18.7 ± 0.3 mm against E. coli, exhibiting lower minimum inhibitory concentration (12.5–50 mg/mL) and minimum bactericidal concentration (25–100 mg/mL) compared to other extracts. Phytochemical screening revealed abundant flavonoids, phenolics, and terpenoids responsible for membrane disruption and enzyme inhibition. Novelty: This research provides empirical evidence of solvent-dependent extraction efficiency from Iraqi cultivars against local clinical isolates. Implications: These findings support the development of cost-effective, environmentally sustainable natural antibacterial agents for pharmaceutical, cosmetic, and food preservation applications, particularly addressing multidrug resistance challenges.Highlight : Ethanolic extract demonstrated highest antibacterial activity against S. aureus and E. coli with lowest MIC and MBC values. Bioactive compounds including flavonoids, phenolics, terpenoids, tannins, and vitamin C contribute to antibacterial mechanisms. Lemon peel extracts showed effectiveness against antibiotic-resistant bacteria, indicating potential for pharmaceutical and food preservation applications. Keywords : Citrus Limon, Lemon Peel, Antibacterial Activity, Multi-Drug Resistance, Natural Antibiotics